Effect of Incisional Negative Pressure Wound Therapy on Surgical Site Infections in High-Risk Reoperative Colorectal Surgery: A Randomized Controlled Trial. Issue 2 (1st April 2022) - Sapci, Ipek; Camargo, Mariane; Duraes, Leonardo; Jia, Xue; Hull, Tracy L.; Ashburn, Jean; Valente, Michael A.; Holubar, Stefan D.; Delaney, Conor P.; Gorgun, Emre; Steele, Scott R.; Liska, David
Abstract : BACKGROUND: Colorectal resections have relatively high rates of surgical site infections causing significant morbidity. Incisional negative pressure wound therapy was introduced to improve wound healing of closed surgical incisions and to prevent surgical site infections. OBJECTIVE: This randomized controlled trial aimed to investigate the effect of incisional NPWT on superficial surgical site infections in high-risk, open, reoperative colorectal surgery. DESIGN: This was a single-center randomized controlled trial conducted between July 2015-October 2020. Patients were randomly assigned to incisional negative pressure wound therapy or standard gauze dressing with a 1:1 ratio. A total of 298 patients were included. SETTINGS: This study was conducted at the colorectal surgery department of a tertiary-level hospital. PATIENTS: This study included patients older than 18 years who underwent elective reoperative open colorectal resections. Patients were excluded who had open surgery within the past 3 months, who had active surgical site infection, and who underwent laparoscopic procedures. MAIN OUTCOME MEASURES: The primary outcome was superficial surgical site infection within 30 days. Secondary outcomes were deep and organ-space surgical site infections within 7 days and 30 days, postoperative complications, and length of hospital stay. RESULTS: A total of 149 patients were included in each arm. The mean age was 51 years, and 49.5% were women. Demographics, preoperative comorbidities, and preoperative albumin levels were comparable between the groups. Overall, most surgeries were performed for IBD, and 77% of the patients had an ostomy fashioned during the surgery. No significant difference was found between the groups in 30-day superficial surgical site infection rate (14.1% in control versus 9.4% in incisional negative pressure wound therapy; p = 0.28). Deep and organ-space surgical site infections rates at 7 and 30 days were also comparable between the groups. Postoperative length of stay and complication rates (Clavien-Dindo grade) were also comparable between the groups. LIMITATIONS: The patient population included in the trial consisted of a selected group of high-risk patients. CONCLUSIONS: Incisional negative pressure wound therapy was not associated with reduced superficial surgical site infection or overall complication rates in patients undergoing high-risk reoperative colorectal resections. See Video Abstract at http://links.lww.com/DCR/B956 . EFECTO DE LA TERAPIA DE HERIDA INSICIONAL CON PRESIÓN NEGATIVA EN INFECCIONES DEL SITIO QUIRÚRGICO EN CIRUGÍA COLORRECTAL REOPERATORIA DE ALTO RIESGO: UN ENSAYO CONTROLADO ALEATORIZADO: ANTECEDENTES: Las resecciones colorrectales tienen tasas relativamente altas de infecciones del sitio quirúrgico que causan una morbilidad significativa. La terapia de heridas incisionales con presión negativa se introdujo para mejorar la cicatrización de las heridas de incisiones quirúrgicas cerradas y para prevenir infecciones del sitio quirúrgico. OBJETIVO: El objetivo de este ensayo controlado y aleatorizado fue investigar el efecto de la terapia de herida incisional con presión negativa en infecciones superficiales del sitio quirúrgico en cirugía colorrectal re operatoria, abierta y de alto riesgo. DISEÑO: Ensayo controlado y aleatorizado de un solo centro entre julio de 2015 y octubre de 2020. Los pacientes fueron aleatorizados para recibir tratamiento para heridas incisionales con presión negativa o vendaje de gasa estándar en una proporción de 1:1. Se incluyeron un total de 298 pacientes. AJUSTE: Este estudio se realizó en el departamento de cirugía colorrectal de un hospital de tercer nivel. PACIENTES: Se incluyeron pacientes mayores de 18 años que se fueron sometidos a resecciones colorrectales abiertas, re operatorias y electivas. Se excluyeron aquellos pacientes que tuvieron cirugía abierta en los últimos 3 meses, con infección activa del sitio quirúrgico y que fueron sometidos a procedimientos laparoscópicos. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue infección superficial del sitio quirúrgico dentro de los 30 días. Los resultados secundarios fueron infecciones del sitio quirúrgico profundas y del espacio orgánico dentro de los 7 y 30 días, las complicaciones posoperatorias y la duración de la estancia hospitalaria. RESULTADOS: Se incluyeron un total de 149 pacientes en cada brazo. La edad media fue de 51 años y el 49, 5% fueron mujeres. La demografía, las comorbilidades preoperatorias y los niveles de albúmina preoperatoria fueron comparables entre los grupos. En general, la mayoría de las cirugías fueron realizadas por enfermedad inflamatoria intestinal y al 77 % de los pacientes se les confecciono una ostomía durante la cirugía. No hubo diferencias significativas entre los grupos en la tasa de infección del sitio quirúrgico superficial a los 30 días (14, 1 % en el control frente a 9, 4 % en el tratamiento de herida incisional con presión negativa, p = 0, 28). Las tasas de infecciones del sitio quirúrgico profundas y del espacio orgánico a los 7 y 30 días también fueron comparables entre los grupos. La duración de la estancia postoperatoria y las tasas de complicaciones (Clavien-Dindo Graduacion) también fueron comparables entre los grupos. LIMITACIONES: La población de pacientes incluida en el ensayo consistió en un grupo seleccionado de pacientes de alto riesgo. CONCLUSIONES: Video Resumen en http://links.lww.com/DCR/B956 . (Traducción—Dr. Osvaldo Gauto )